ANTESEDEN PARTISIPASI ANGGARAN: GAYA KEPEMIMPINAN, ASIMETRI INFORMASI, DAN PENGGUNAAN REALISASI ANGGARAN SEBAGAI ALAT EVALUASI (STUDI KASUS SATKER DI WILAYAH PEMBAYARAN KPPN SELONG) - Fauzi, Achmad; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2013)
The main purpose of this study is to explore the causes or antecedents of budget participation in the public sector organization. The study focuses on the reasons why superiors encourage the budget participation of their subordinates and use several theoretical perspectives including leadership theory, agency theory and organizational justice. Data used in this study is obtained using questionnaires method. From 120 questionnaires which were distributed to the treasury managers in government offices under the KPPN Selong budgets payment area, 88 (73,33 %) questionnaires were sent back but only 69 questionnaires could be used for analyse. The data was analyzed with Multiple Linear Regression using IBM SPSS 16 program. The result of this study proves that evaluative use of budget realization has positive and significant relationship with superiors encourage of budget participation, in which case, the study argues, the superiors encourage participation because of concerns about organizational justice. This study also found that the evaluative use of budget realization and budget participation relationship are significantly mediated by superiors encourage in budget participation as an intervening variable. The two hypothesis about relationship between considerate leadership style with superior encourage budget participation and relationship between information asymmetry with superior encourage budget participation is not supported.